Anterior teeth restoration after endodontic treatment and vital teeth with porcelain veneers and eLab Prime system - O. S. Mordanov; A. I. Matveev (Эндодонтия Today)
Clinical complications arising from problems related to aesthetic integration can be a difficult task for the restorative dentist and dental technician. Accurate imitation of the optical appearance of dental hard tissue with indirect restorations is a relevant issue, especially when teeth have different color shades. This case report describes the approach to restoring the anterior group of teeth with porcelain veneers and the eLAB prime software.